Development and evaluation of basaltic volcanic ash based high performance concrete incorporating metakaolin, micro and nano-silica - Kaffayatullah Khan; Megat Azmi Megat Johari; Muhammad Nasir Amin; Muhammad Nasir (Developments in the Built Environment, 2024)
High-performance concrete is an excellent choice for modern engineering structures due to its superior performance, low maintenance costs, and long service life. Therefore, this study was aimed to produce high-performance concrete by incorporating a high volume of basaltic volcanic ash along with metakaolin (MK), micro-silica (MS), and nano-silica (NS). An investigation was performed in regard to the mechanical and durability properties, autogenous and drying shrinkage, and microstructural and pore-structure properties. A control mix, binary mixes, and ternary mixes were examined. The binary mixes contained fine (VA) and ultra-fine (VAF) volcanic ashes, and the ternary mixes contained combinations of VA with MK, MS, and NS. Test results show that ternary mixes with 30% and 40% cement substitution demonstrated better strength development and higher resistance to chloride penetration and water absorption. All binary and ternary mixes displayed lower autogenous shrinkage, as well as lower or comparable drying shrinkage than the control mix. Moreover, the combination of VA with MK, MS, and NS up to 40% resulted in micro and pore structure refinement by forming high-density gels. The findings indicate that VA in combination with MK, MS, and NS, can effectively substitute cement at up to 40% for the production of sustainable high-performance concrete.